KEJADIAN DIARE PADA BALITA - Hendra Mukhlis (Program Studi Ilmu Lingkungan, Program Pascasarjana Universitas Riau, 2020)
Diarrheal disease still became one of the public health problem, because it is the third contributor to the number of pain and death of children in various countries. Diarrheal disease in children is the most cases of the disease that exist in almost every hospital that type B than cases of other diseases. Cases of diarrhoea are recorded as much as 32.25% were children aged under two years. This research aims to know the factors associated with the incidence of diarrhea in toddlers. This research by using a quantitative approach with cross sectional design. The population is mempuanyai mother children aged 0 – 24 months hospitalized. With the samples as many as 60 people, the data collected through interviews with guide questionnaire, then processed in a computerized using statistical test chi-square. The results of the univariate analysis known 41.7% treated children aged 0-24 months experiencing diarrhea, 55.0% of the respondents have a good knowledge of about diarrhea, 53.5% of the respondents have a positive attitude-related diarrhea, 50.0% of the respondents have a good behavior about breast feeding and 55.0% havebehavior that is not well related awarding of MP-ASI. The result is there is no relationship Bivariat knowledge with the incidence of diarrhoea (p value = 0.148), there was no relationship attitude with diarrhea (p value = 0.484) and there is a relationship of the behavior of breast feeding (p value = 0.004) and MP-ASI giving of behavior with the incidence of diarrhoea (p value = 0.000). Expected to mothers who have children toddlers in order to pay attention to nutrition in breast feeding and giving of the MP-ASI is also about children's environmental health in General so that the children are spared from the disease.